RANCANG BANGUN PROTOTYPE ALAT SISTEM KERJA TANGKI DISTRIBUSI AIR ARTESIS BERBASIS PLC - -, Jujun; -, Yurika (Jurnal Mahasiswa Terapan, 2024)
Water is an essential element in human life, especially in household activities such as washing and cooking. In Indonesia, many areas depend on artesian water sources, but access to water is not always evenly distributed and often must follow a certain schedule. This requires an efficient control system to facilitate water distribution management. This research proposes the design of a simulation tool to automate the control of reservoir filler motors and water distribution valves using a Programmable Logic Controller (PLC). The main purpose of this tool is to make it easier for artesian water managers or officers by controlling the solenoid valve remotely and monitoring the status of the motor and the water level in the holding tank automatically. This system allows monitoring motor status via panel indicators and ensures valves operate according to control from the PLC. Additionally, the water level can be monitored with sensors connected to the PLC. This research underlines the importance of implementing modern control systems in industry, and provides recommendations for further development, including the implementation of PID control for efficiency and the use of flow meters to measure water flow rates.